INSULIN RESISTANCE: GOOD OR BAD? DEVELOPMENT MECHANISMS AND THE ASSOCIATION WITH AGE-RELATED VASCULAR CHANGES - S. A. Boytsov; I. D. Strazhesko; D. U. Akasheva; E. N. Dudinskaya; A. S. Kruglikova; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика)
The authors discuss the mechanisms of insulin resistance (IR) development; the IR role in the development and progression of the major age-related vascular changes; IR and the transformation of vascular ageing into disease; and IR impact on life expectancy.